OBIS. Optimising Bike Sharing in European cities. A handbook. - (:unkn) unknown (My University, 2011)
Three years research on more than 50 bike sharing schemes in ten European countries, visualised in 27 tables and 73 figures, results and recommendations summarised on around 100 pages: That is the OBIS handbook, the final product of the most comprehensive research project on bike sharing schemes so far. The OBIS handbook presents interesting facts and figures from the world of bike sharing. Scheme characteristics such as technology, scheme size, service design etc. are described in connection with external factors of the cities. Finally the handbook gives comprehensive advice for all three stages in the lifetime of a BSS: Planning, Implementation, Optimisation. The OBIS handbook is useful for local, regional and central governments involved in traffic issues, bike sharing providers and other companies and organisations related to bike sharing (such as providers of street furniture, outdoor advertisers, municipal parking operators), public transport operators, urban planners and cycling organisations.
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Stadtverkehr; Bike-Sharing; Fahrradverleih; öffentliches Fahrradverleihsystem; Fahrradbenutzung; Handlungsempfehlung